2021
DOI: 10.3947/ic.2021.0094
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Personal Protective Equipment among Frontline Nurses in a Nationally Designated COVID-19 Hospital during the Pandemic

Abstract: Background The appropriate use of personal protective equipment (PPE) can significantly reduce the risk of infection associated with caring for patients. This study aimed to investigate the knowledge, awareness, and behaviors related to the PPE usage among frontline nurses in a nationally designated coronavirus disease 2019 (COVID-19) hospital during the COVID-19 pandemic. Materials and Methods The study was performed in two phases: (1) a questionnaire survey to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Among the personal protective equipment, nurses perceived goggles as creating the most discomfort. In a previous study (Min et al, 2021), more than half of frontline nurses reported discomfort from wearing goggles and did not help prevent COVID‐19 infection. Goggles created discomfort when working with patients due to obscured vision from its fogging, which was stressful for nurses (Kim & Lee, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Among the personal protective equipment, nurses perceived goggles as creating the most discomfort. In a previous study (Min et al, 2021), more than half of frontline nurses reported discomfort from wearing goggles and did not help prevent COVID‐19 infection. Goggles created discomfort when working with patients due to obscured vision from its fogging, which was stressful for nurses (Kim & Lee, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…However, donning personal protective equipment for a long period can be cumbersome and uncomfortable and result in headaches, overheating, trouble with verbal communication, impaired visibility and back pain related to powered air‐purifying respirators use (Loibner et al, 2019; Ong et al, 2020). Although research has established the association between inadequate personal protective equipment use and increased risk of COVID‐19 infection (Nguyen et al, 2020), perceived discomfort from personal protective equipment may discourage health care workers' willingness to work during the COVID‐19 pandemic (Min et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that most hospitals provided coveralls as PPE for healthcare workers managing confirmed COVID-19 cases. A Korean study showed that even though most healthcare workers knew that the Korea Disease Control and Prevention Agency (KDCA) guidelines allowed healthcare workers to choose either coveralls or long-sleeved gowns, many healthcare workers did not use long-sleeved gowns [ 28 ]. This might be attributable to confusion among healthcare workers about COVID-19 transmission due to the initial KDCA recommendation about PPE; at the beginning of the pandemic, KDCA recommended using coveralls during managing COVID-19 patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Personal protective equipment (PPE) is essential in the protection and spread of the COVID‐19 virus as SARS‐CoV‐2 is transmitted through respiratory droplets and close contact (Park, 2020 ). At the beginning of the pandemic, there was much discussion as to what the proper and most protective forms of PPE were (Hussain et al, 2020 ; Min et al, 2021 ). This uncertainty, although unavoidable, likely created a delayed response time to patient care, as more time was needed between patients to assure proper PPE and safety protocols could be followed by HCWs.…”
Section: Introductionmentioning
confidence: 99%